How Mindfulness Influences the Relationship Between Affective Daily Events and Well-being at Work - Junça Silva, A.; Caetano, António; Lopes, M. (13th European Academy of Occupational Health Psychology Conference, 2018)
Purpose: Mindfulness is characterized by an active mindset determined by novel-distinction drawing resulting in being more situated in the present moment, more sensitive to the context and to the different experiences, and also guided by rules and routines. Research on mindfulness has generally shown that its causes relate to characteristics of both the individual and the work experiences. Diverse studies have also demonstrated that mindfulness has benefitial effects regarding health and well-being. Despite its importance, empirical studies exploring mindfulness at work are scarce. Plus, the role that mindfulness plays on the relationship between work-related daily events and well-being is unknown. Thus, we aim to explore the relationship between work-related daily events, mindfulness and well-being. We propose a model suggesting that work-related daily events induce immediate affect, and that those affective states enhance or decrease well-being. We further propose that mindfulness can mitigate negative affect and its negative outcomes, and that it can broad the positive effects of positive affect on well-being. Design: A diary study with workers (N = 52) from diverse job sectors. Individuals reported daily events, immediate affect and wellbeing for four consecutive working days. Results: Results support our model and suggest that diverse work-related daily events increase the likelihood to experience affective states at work which, in turn, will influence workers’ well-being. Plus, mindfulness buffers the negative effects that daily hassles have on employees’ well-being, and enhances the positive effects that daily uplifts have on well-being. Limitations: The self-reported nature of the data, and the sample size limits the generalization of our results. Practical Implications: This study extends previous findings on mindfulness at work and its consequences for employees’ well-being. In particular, results evidence the relevant role that mindfulness practices may have to mitigate the negative effects of daily hassles in the workplace. Originality: This study is one of the first daily studies on mindfulness applied to organizational settings. Plus, it establishes a link between specific work-related daily events to mindfulness, and well-being.